PENGARUH PEMBERIAN BALANCE EXERCISE TERHADAP PENINGKATAN POSTURAL PADA LANSIA DI PUSTU DESA SIRATAH KEC.SILIMA PUNGGA-PUNGGA TAHUN 2020 - Lili Suryani Tumanggor (Jurnal Penelitian Keperawatan Medik, 2020)
Elderly is the final stage of the aging process. The process of getting old will be experienced by everyone. Aging is a process that every human goes through, and the aging process is the last human life, where at this time a person will experience physical, mental and social setbacks gradually so that they cannot carry out their daily tasks or are often called physical setbacks. Balance exercise is a special exercise or a movement that is used to improve the ability of muscles to maintain body balance. According to Word Health Organitation (WHO) the prevalence falls at the age of 65 years and over around 28-35% and at the age of 70 years and over around 32-42%. The prevalence of the elderly falls in the United States, every year one in five events falls due to impaired balance causing serious injury. Most head injuries (47%), upper limbs (28%) and lower limbs (26%) Kota Medan 61.5%, Karo 27.1%, Pakpak Bharat 50.0%, Kota Pematang Siantar 35.4%, Kota Tebing Tinggi 39.4%, Kota Binjai 49.5%, and in Dairi 36.5%. The purpose of this study was to determine the Effect of Giving Balance Exercise to Postural Improvement in the Elderly in Pustu Desa Siratah, Kec. Silima Pungga-pungga Kab. Dairi Tahun 2020. The type of research used is quantitative research with pre-experimental research design, using pre-test and post-test design. The sampling technique used in this study was using purposive sampling technique obtained 10 samples in this study. Analysis of data using the Wilcoxon Test. The results of data analysis obtained p-value = 0.003 < alpha (α) = 0.05. The results of this study are that there is an effect of the provision of balance exercise on postural improvement in the elderly in Pustu Desa Siratah, Kec. Silima Pungga-pungga in 2020.